Determinan Yang Mempengaruhi Peningkatan Kinerja Womenpreneur Dalam Berwirausaha - Karimah, Isnah; Nurhayati, Siti; Sunarjo, Wenty Ayu (LPPM Universitas Pekalongan, 2024)
Women have a big role in increasing national economic growth through entrepreneurial activities. The purpose of this study is to determine the effect of flexible work arrangements and work-life balance on womenpreneur performance through entrepreneur commitment. The type of this research is associative research with a quantitative approach. The sample in this study consists of 120 womenpreneurs who run the business in Pekalongan. Data collection techniques use the survey method by distributing questionnaires. Data analysis uses the SEM PLS. The result of the analysis shows that flexible work arrangements and work-life balance have a significant positive effect on womenpreneur performance through entrepreneur commitment. The R square value is 0.769 shows that flexible work arrangement and work-life balance have an effect of 76.9% on women's performance and the rest 20.6% is influenced by other variables not included in this study. The other variable that can be add for the future research are entrepreneurship characteristics, locus of control, human resource competence, education and motivation.